Impact of the COVID‐19 pandemic on initial weight loss in a digital weight management program: A natural experiment. Issue 9 (30th July 2021) - Bullard, Tiffany; Medcalf, Adam; Rethorst, Chad; Foster, Gary D.
Abstract: Objective: The aim of this study was to assess the impact of the coronavirus disease 2019 (COVID‐19) pandemic on initial weight loss during a digital weight management program. Methods: Participants ( n = 866, 192; BMI 33.6 [SD 7.4] kg/m 2 ) who joined a digital weight management program (WW) in the first 30 weeks of 2020 (COVID‐19 cohort) were compared with participants ( n = 624, 043; BMI 33.1 [SD 7.2] kg/m 2 ) who joined the same program during the same time period in 2019 (control cohort). Weight change (percentage) and self‐monitoring over the first 4 weeks of enrollment were compared between the cohorts. Significance was defined as meeting the criteria for a small effect ( d ≥ 0.2). Results: Over the 30‐week enrollment period, the COVID‐19 cohort experienced significantly less weight loss than the control cohort but only for 7 weeks of enrollments. The COVID‐19 cohort also had fewer days of food tracking but only for 3 weeks of enrollments. There were no differences in the self‐monitoring of weight and activity at any time between the two cohorts. Conclusions: Over a 30‐week enrollment period, COVID‐19 had negative effects on both weight loss and food self‐monitoring, but the effects were short‐lived. Those participating in evidence‐based weight management programs can expect similar levels of initial weight loss as those experienced before the pandemic.